Penerapan Practical Life pada Metode Montessori dalam Mengembangkan Aspek Kemandirian Anak Usia Dini di Bumi Abdi Montessori School Tangerang Banten - Siti Munawaroh; Siskandar Siskandar; Akhmad Shunhaji (Lembaga Pengembangan Kinerja Dosen, 2026)
This study discusses the application of discipline in the Montessori method and efforts to increase children's independence through Practical Life activities. The results of research at Bumi Abdi Montessori School show that discipline began to be introduced through basic classroom rules, the granting of freedom accompanied by responsibility, and self-control exercises. Children have gained an initial understanding, although they still need assistance so that independence is formed more consistently. In this context, Practical Life activities are present as an effective strategy to support children's development. Through daily activities, such as taking care of themselves, maintaining cleanliness, managing the environment, and interacting politely, children are trained to be independent while getting used to living an orderly life. With consistent application from teachers and parental support, Practical Life not only helps to foster discipline, but also affirms the main goal of Montessori, which is to form children who are able to manage themselves independently. The research method uses a descriptive qualitative approach with the stages of identification, collection, analysis, and interpretation of visual and narrative data in depth to understand the phenomenon being studied.